Aftermath of COVID-19 – the impact on sustainability in container shipping (economic sustainability) - Lau, Sarah Xue Ying (Nanyang Technological University, 2023)
When the COVID-19 pandemic first hit in December 2019, the world was taken by surprise. The pandemic has since left devastating impacts on the global economy and disrupted supply chains. Undoubtedly, the shipping industry also experienced an upheaval due to the pandemic, most notably in the container shipping market. Skyrocketing freight rates at the peak of COVID-19 drew the world’s attention to the container market. This has also highlighted the importance of shipping, the world’s reliance on shipping, and in particular, the power of carriers. However, it remains unclear as to whether the effects of this unprecedented economic boom are here to stay. This study aims to explore the impact of the COVID-19 pandemic on the three pillars of sustainability in container shipping, namely Social, Environmental and Economic Sustainability. This paper will focus on the post-pandemic impact on the economic sustainability of container shipping. It will also investigate container carriers’ responses and strategies in view of the post-pandemic outlook. A literature review was carried out to review the economic sustainability before, during and after the pandemic. Various operational decisions and strategies adopted by carriers were also compared throughout this period. Interviews and surveys were conducted to gather the perspectives of different stakeholders. The results of the perception survey were then analysed using the Wilcoxon Signed Rank Test to assess the significance of the results. From our research and analysis, it was concluded that the pandemic had brought about both challenges and opportunities for economic sustainability in container shipping. However, the fundamental problem of imbalances in supply and demand still persists post-pandemic. Freight rate levels have gradually returned and stabilised back around pre-pandemic levels after experiencing intensive fluctuations amid the pandemic. Changing consumer behaviour has resulted in weak demand volumes while the influx of container newbuilds has further depressed current markets. Disruptions in supply chains, port congestions and schedule reliability have also generally recovered to pre-pandemic conditions. From the pandemic disruption, carriers have also learnt to employ various capacity management measures and have been effectively using these measures to achieve their required capacity adjustments. In conclusion, a positive progress on sustainability has been generally noted as economies recover and normalise in the aftermath of the COVID-19 pandemic.